Electron Microscopy of Vesicular Stomatitis Virus Replicative Ribonucleoproteins - Naeve, Clayton W. (1980)
The objective of this investigation was to examine by electron microscopy the replicative ribonucleoprotein (RNP) structures synthesized in vesicular stomatitis virus-infected HeLa cells. Pulse-labeled in vivo products of vesicular stomatitis virus replication and transcription can be separated by centrifugation in Renografin gradients. Transcription complexes are dissociated, allowing nascent messenger RNPs to remain at the top of the gradient, whereas RNPs biochemically consistent with replication complexes sediment to the middle of the gradient. Examination of these structures by electron microscopy revealed that all exist as coiled or helical RNPs having dimensions of ∼20 by 700 nm. These structures can be further subdivided into three major morphological classes: (i) linear forms (20 by 769 ± 158 nm), which have both ends free; (ii) circular forms (20 by 679 ± 95 nm), which appear to have both ends joined; and (iii) complex forms, which include those structures which are branched replicative complexes as well as those which are random. To distinguish random complexes and possible transcriptive complex contaminants from replicative complexes, it was necessary to uncoil the RNP structures with EDTA so that length measurements could be made relating the nascent strand length to its position on the template. After EDTA treatment, the linear RNPs uncoiled (10 by 4,035 ± 3,802 nm), and the circular morphology virtually disappeared. However, a new form appeared which was one-half the length and double the width (20 by 2,103 ± 306 nm) of full-length RNPs and contained a loop at one end and two free ends at the other (α-form RNP). The distribution and length analysis of these structures, plus and minus EDTA, suggest that the α-form RNPs arise by EDTA-induced uncoiling of circular forms held together at the ends. Close scrutiny of uncoiled complex RNPs revealed no single-strand RNP templates with single-strand nascents. However, several complexes were observed which appeared to contain α-form templates with single-strand nascent RNPs. Length measurements suggest these complexes are neither random nor transcriptive, but are replicative. These experiments suggest that replication may, in part, occur on circular coiled RNP templates.